An omega-3 Fatty Acid Enriched Diet Reduces Anxiety-like Behavior While High Dietary Sucrose During Chemotherapy Increases Anxiety-like Behavior in Mice (P14-023-19). (13th June 2019) - Ormiston, Kate; Orchard, Tonya; DeVries, A Courtney; Phuwamongkolwiwat, Panchitaa; Li, Jinhui; Andridge, Rebecca; Fitzgerald, Julie; Tinkai, Tial; Lustberg, Maryam
Abstract: Objectives: Incidence of anxiety is nearly three times higher in breast cancer patients compared to healthy women, and chemotherapy may increase risk. Chemotherapy-induced neuroinflammation may contribute to anxiety. Omega-3 fatty acids (n-3 FAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), improve symptoms of anxiety in some studies. However, the effects of n-3 FAs on anxiety during chemotherapy have not been examined. We hypothesized that a diet enriched with n-3 FAs and low in sucrose would significantly improve anxiety-like behavior in chemotherapy treated mice. Methods: Female, ovariectomized C57BL/6 mice (7–8 weeks old) were randomly assigned to one of four diets: 2% kcal EPA + DHA or no EPA + DHA with low sucrose or high sucrose. After two and four weeks of diets, mice received a saline or chemotherapy injection (9 mg/kg doxorubicin + 90 mg/kg cyclophosphamide), then continued on diets. Seven days after the second injection, mice completed a marble burying test to assess anxiety-like behavior and were sacrificed 10 days later. Significant differences ( P < 0.05) were determined using negative binomial regression models. Gene expression of inflammatory cytokines in the hippocampus and cortex was measured using PCR. Spearman correlations assessed associations of cytokines with anxiety. Results: Twenty-one % of mice completely buried (i.e., 100% buried) at least one marble; 85% of mice partially buried (>50% but <100% buried) at least one marble. There was a significant n-3 FA effect on number of marbles 100% buried ( P = 0.01); fewer marbles were buried by the 2% EPA + DHA group, indicative of less anxiety-like behavior in these mice. There was a significant interaction effect of injection and sucrose on number of marbles 100% buried ( P = 0.03); in the chemotherapy group, mice fed low sucrose completely buried fewer marbles than mice fed high sucrose ( P < 0.001), but in the saline group, there was no significant difference. There was a significant negative correlation ( r = −0.24, P = 0.04) between interleukin-6 in the cortex and number of marbles partially buried. Conclusions: Our findings suggest that dietary EPA + DHA reduces, while sucrose and chemotherapy increase, anxiety-like behavior in our mouse model. Future studies should investigate underlying mechanisms. Funding Sources: National Cancer Institute.